2003
DOI: 10.1128/jvi.77.4.2459-2468.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Molecular Characterization of the RNA Polymerase-Binding Motif of Infectious Bursal Disease Virus Inner Capsid Protein VP3

Abstract: Infectious bursal disease virus (IBDV), a member of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
47
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…The presence of M3 at the IBDV assembly factories might hamper the correct incorporation of the VP1 polypeptide into the newly formed particles. This hypothesis is supported by the previous observation that treatment of IBDV-infected cells with Trojan peptides containing the VP1-binding motif found in VP3 causes a significant reduction in infective-virus production (6).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The presence of M3 at the IBDV assembly factories might hamper the correct incorporation of the VP1 polypeptide into the newly formed particles. This hypothesis is supported by the previous observation that treatment of IBDV-infected cells with Trojan peptides containing the VP1-binding motif found in VP3 causes a significant reduction in infective-virus production (6).…”
supporting
confidence: 76%
“…This dramatic alteration in the M3 subcellular distribution strongly suggests that it participates in the assembly of the virus progeny. Previous studies have shown that although M3 is unable to form complexes with the virus-encoded RNA-dependent RNA polymerase (6), it retains the ability to oligomerize (7) and to interact with the virus genome (4). The presence of M3 at the IBDV assembly factories might hamper the correct incorporation of the VP1 polypeptide into the newly formed particles.…”
mentioning
confidence: 99%
“…VP2 and a variable amount of pVP2 assemble into 260 trimers to form the capsid structural units (accounting for Ϸ38 MDa); VP3 is a multifunctional protein that interacts with itself (14), pVP2 (11), VP1 (15,16), and with the dsRNA to make ribonucleoprotein complexes (17), a unique feature among dsRNA viruses.…”
mentioning
confidence: 99%
“…The VP3 C terminus, which also participates in VP1 incorporation into the capsid, serves as a transcriptional activator (22) because it removes the inherent structural blockade of RNA polymerase activity. In addition, the VP3 oligomerization domain maps within the 42 C-terminal residues of the polypeptide (23). Finally, VP3 is also an RNA-binding protein associated with the dsRNA genome (34,45).…”
Section: Discussionmentioning
confidence: 99%
“…The released C-terminal segments remain associated with the capsid (15) and, by promoting the disruption of host cell membranes, appear to be involved in the entry mechanism (16,17). VP3 is a multifunctional protein that interacts with itself (18,19), pVP2 (20,21), VP1 (22)(23)(24), and the dsRNA (25,26).…”
mentioning
confidence: 99%